Screening of immunosuppressive factors for biomarkers of breast cancer malignancy phenotypes and subtype-specific targeted therapy - Wang,Ping; Liu,Jiaxuan; Song,Yunlei; Liu,Qiang; Wang,Chao; Qian,Caiyun; Zhang,Shuhua; Zhu,Weifeng; Yang,Xiaohong; Wan,Fusheng; Liu,Zhuoqi; Luo,Daya (PeerJ, 2019)
We aimed to screen and validate immunosuppressive factors in luminal- and basal-like breast cancer cell lines and tissue samples associated with malignant phenotypes. The mRNA microarray datasets, GSE40057 and GSE1561, were downloaded and remodeled, and differentially expressed genes were identified. Weighted gene co-expression network analysis (WGCNA) and gene ontology (GO) and KEGG pathway enrichment analysis were performed to explore the immune-related events related to the basal-like breast cancer. The online resources, GOBO, Kaplan–Meier Plotter and UALCAN, were employed to screen for immunosuppressive factors associated with breast cancer malignant phenotypes. Immunohistochemistry was used to evaluate VEGFA and MIF levels in breast tumors and normal breast tissues; qPCRs and western blots were used to validate the expression of clinical immuno-oncology (IO) therapeutic targets CD274 (PD-L1) and IL8 in cell lines. The results showed that various immune-related events contribute to basal-like breast cancer. First, TGFβ1 and IL8 had higher average expression levels in more malignant cell lines; second, MIF and VEGFA had higher average expression levels in more malignant breast cancer tissues, and the high expression levels were associated with poor survival rate. Third, IO targets CD274 and IL8 which were confirmed to be more suitable for the treatment of basal-like breast cancer. In view of the above, during the formation and development of breast cancer, immune-related genes are always activated, and immunosuppressive factors, IL8, TGFβ1, MIF, and VEGFA are up-regulated. Such molecules could be used as biomarkers for breast cancer prognosis. However, because individual immune-related factors can play several biological roles, the mechanistic relationship between immunosuppressive factors and breast cancer malignant phenotypes and the feasibility of their application as drug targets require further investigation.
Keywords: Breast cancer; Immunosuppressive factor; Biomarker; Therapeutic target; Online databases